2017
DOI: 10.3233/thc-161259
|View full text |Cite
|
Sign up to set email alerts
|

Development of a mobile application for oral cancer screening

Abstract: Mobile apps including videos and data collection interfaces could be an interesting alternative in oral cancer research development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 8 publications
0
32
0
3
Order By: Relevance
“…17 In terms of the populations and regions, 7 studies (30.4%) had a significant number of mHealth usage in remote regions with limited infrastructure for Salmani et al 3 high-risk populations, remote clinical diagnosis and remote patient monitoring. 9,15,22,26,30,32,33 The remote mHealth approach is a step towards a more successful oral cancer screening programme 32 and also maintenance of patient records for follow-up. 33 Seven studies (30.4%) had reported that mHealth improves healthcare quality in remote regions.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…17 In terms of the populations and regions, 7 studies (30.4%) had a significant number of mHealth usage in remote regions with limited infrastructure for Salmani et al 3 high-risk populations, remote clinical diagnosis and remote patient monitoring. 9,15,22,26,30,32,33 The remote mHealth approach is a step towards a more successful oral cancer screening programme 32 and also maintenance of patient records for follow-up. 33 Seven studies (30.4%) had reported that mHealth improves healthcare quality in remote regions.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Three studies dealing with apps in teh context of head and neck cancer could be retrieved [72][73][74]. In one article, a patient cohort that also included head and neck cancer patients was asked by means of a questionnaire if they could imagine that cancer therapy and also the quality of life could be monitored and probably even controlled by an app [72].…”
Section: Studies On Apps Regarding Head and Neck Cancermentioning
confidence: 99%
“…Thus, the app will be further improved in order to achieve a sustainable increase of the quality of life. The early detection of head and neck can-cer as well as its improvement by means of an app were discussed in another study [73]. In this app, a questionnaire is filled out regarding risk factors for the development of head and neck cancer, such as for example noxae or unprotected oral sex.…”
Section: Studies On Apps Regarding Head and Neck Cancermentioning
confidence: 99%
“…O estudo realizado por Farias e Pereira 13 teve como objetivo analisar a discrepância de massa dentária de Bolton através da comparação entre a análise digital (bidimensional) com a análise manual (padrão-ouro) de 75 pares de modelos de gesso. No estudo desenvolvido por Gomes et al 14 , essa avaliação foi feita por meio de comparações entre os dados coletados pelo aplicativo e de exames padrões. Em ambas as comparações os aplicativos tiveram grande precisão em relação ao método padrão.…”
Section: Figura 1 Fluxograma Do Preferred Reporting Items For Systemunclassified
“…A usabilidade dos aplicativos, ou seja, a facilidade com que os usuários têm de empregar as ferramentas, foi testada em três estudos. No sistema de rastreio de câncer bucal 14 Os autores destacam a importância de cirurgiões-dentistas e profissionais da informática trabalharem em conjunto.…”
Section: Figura 1 Fluxograma Do Preferred Reporting Items For Systemunclassified